PROSPECTS OF IMPROVEMENT THE CONSTRUCTION FOR PLANTING ENERGY CROPS - Єрмаков, С. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Energy planting crops has much in common with the process of seedling planting and forest-planting. Existing models of machines for planting energy crops have several disadvantages associated primarily with using manual labor. The methodology of finding promising solutions based on qualitative analysis of material presentation of various types of planting machines; periodical reviews and published literature is given in the study. The research is based on available descriptive and video materials; allowing you to organize experience and develop new recommendations. The methods of structure and factor analysis; system approach; abstraction were used in the paper. Results of the developed method are marked by characteristic features of different types of machines; which in its conceptual framework focuse on planting the cuttings of energy crops.